Complement inhibition as potential new therapy for antibody‐mediated rejection. (10th November 2015) - Eskandary, Farsad; Wahrmann, Markus; Mühlbacher, Jakob; Böhmig, Georg A.
Summary: Antibody‐mediated rejection (ABMR) is a leading cause of kidney allograft failure. While the exact mechanisms contributing to donor‐specific antibody (DSA)‐triggered tissue injury are still incompletely understood, complement activation via the classical pathway is believed to be one of the key players. There is now growing interest in complement blockade as an antirejection treatment. One attractive strategy may be inhibition of terminal complex formation using anti‐C5 antibody eculizumab. Anecdotal reports, case series, and a unique cohort of flow crossmatch‐positive live donor kidney transplant recipients subjected to eculizumab‐based desensitization have demonstrated successful prevention and reversal of acute clinical ABMR. Nevertheless, maybe due to complement activation steps proximal of C5 or even complement‐independent mechanisms, subclinical rejection processes that might culminate in chronic injury were found to escape inhibition. Larger studies designed to clarify the actual clinical value of terminal complement inhibition as an antirejection treatment are currently underway. In addition, alternative concepts, such as therapies that target key component C1, are currently under development, and we will see in the near future whether new strategies in the pipeline will have the potential to beneficially impact clinical practice.